Issues of Women's Rights in the Jadid Movement - Nilufar D. Djuraeva (Indonesian Journal of Cultural and Community Development, 2024)
This article delves into the Jadidist movement's influence on women's rights and gender equality within Uzbekistan, emphasizing the pivotal role of enlightened women in societal development. Through the lens of the Jadids' mantra of "Freedom, equality, justice," this study examines their educational endeavors aimed at fostering intellectual growth, political literacy, and a heightened sense of legal consciousness among women. The research reveals a congruence between Jadidist ideals and the aspirations of the New Uzbekistan, highlighting their mutual commitment to societal progress. Employing qualitative analysis, this study elucidates the transformative impact of the Jadidist movement on women's political culture and participation. The findings underscore the significance of aligning progressive ideologies with policy frameworks for advancing gender equality and social development in Uzbekistan and beyond Highlights: The Jadidist movement in Uzbekistan promotes women's rights and gender equality through education and political activism. Enlightened women play a crucial role in advancing societal development within the Jadidist framework. Alignment between Jadidist ideals and the goals of the New Uzbekistan signifies a promising avenue for enhancing gender equality and political participation. Keywords: Modern, Progressive, Society, Women, Education